2011
DOI: 10.1097/shk.0b013e3182184ee7
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Microflora Contribute to Host Defense Against Escherichia Coli Pneumonia Through Toll-Like Receptors

Abstract: The influence of the gut-lung axis on the lung immunity, although appreciated, remains undefined mechanically. This study was designed to investigate whether commensal microflora in gut increase host defense against subsequent pneumonia through toll-like receptor (TLR) signaling and if oral TLR4 ligand supplementation enhances lung defense against bacterial challenge. We found that commensal gut depletion by antibiotic pretreatment before Escherichia coli pneumonia challenge induced a 15-fold and a 3-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 35 publications
1
65
0
1
Order By: Relevance
“…As the current study focused on the very immediate response to infection, this does not preclude the possibility that the upper airway microbiota, or TLR ligands, regulate other aspects of lung immunity important at later time points during infection. For example, other studies have shown that in the absence of signals from the microbiota, there is increased mortality during bacterial lung infection, and this could be rescued by LPS administration either in the drinking water or via intraperitoneal injection (21,61). These studies analyzed later time points in infection than this study and did not address the role of NLRs, but they do raise the possibility that TLR ligands regulate other components of lung immunity important during the later stages in lung infection.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As the current study focused on the very immediate response to infection, this does not preclude the possibility that the upper airway microbiota, or TLR ligands, regulate other aspects of lung immunity important at later time points during infection. For example, other studies have shown that in the absence of signals from the microbiota, there is increased mortality during bacterial lung infection, and this could be rescued by LPS administration either in the drinking water or via intraperitoneal injection (21,61). These studies analyzed later time points in infection than this study and did not address the role of NLRs, but they do raise the possibility that TLR ligands regulate other components of lung immunity important during the later stages in lung infection.…”
Section: Discussionmentioning
confidence: 74%
“…The mechanistic basis for these distal influences, the precise cellular functions in innate cells regulated systemically by commensal bacteria, and the impact this has on host defenses to bacterial infection outside the intestine have been incompletely characterized. Previous studies have shown increased mortality from bacterial infection in the lung in the absence of the microbiota (21,61), but the specific immune defects that cause this are poorly understood. Data presented here show that the antibacterial activity of alveolar macrophages is compromised in the absence of the commensal microbiota, leading to defects in early bacterial clearance from the lung, which can be restored by administration of bacterial NLR ligands via the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that in mice without a microbiota (germ‐free) K. pneumoniae lung infection causes significantly higher rates of mortality than in mice with a microbiota 62. Similar defects in lung defences were also seen in a model of Escherichia coli lung infection 63. This suggests that microbes in the gastrointestinal tract can have a systemic influence on antibacterial defences at distal mucosal sites and this occurs through PRR activation.…”
Section: Host Resistance To Airway Infection and The Microbiotamentioning
confidence: 74%
“…IL-6-deficient mice showed an impaired defense against pneumococcal pneumonia (47). Interestingly, IL-6 and IL-1b levels are elevated in mice orally treated with antibiotics resulting in commensal depletion compared to those in untreated mice and are associated with more severe illness (21). This is in accordance with our findings that sfb-negative mice had lower IL-6 levels than sfb-positive mice 8 h after infection and that initially sfb-negative mice had markedly increased IL-6 expression after acquisition of sfb.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the GI microbiota on lung immunity, the so-called gut-lung axis, has recently become the focus of more interest, but the underlying mechanisms are still incompletely understood (20). Commensal organisms of the GI tract contribute to the host defense against Escherichia coli pneumonia via Toll-like receptor (TLR) signaling (21), and germfree mice have a strikingly higher mortality rate than that of conventional mice following P. aeruginosa pneumonia (22). Little is known regarding the role of specific organisms in modulating pulmonary immunity and whether the gastrointestinal microbiota has any influence on Gram-positive lung pathogens, or S. aureus in particular.…”
mentioning
confidence: 99%